2020
DOI: 10.1080/10350330.2020.1762986
|View full text |Cite
|
Sign up to set email alerts
|

The commodification of motherhood: normalisation of consumerism in mediated discourse on mothering

Abstract: This paper critically explores how contemporary practices of commercialised self-mediation by "celebrity mothers" increasingly normalise a strongly commodified and consumption-driven vision of motherhood. Drawing on the affordances of mediatisation and self-mediation embedded in the wider neoliberal and celebrity culture mindset, the article analyses how motherhood becomes increasingly linked, in public discourses, to economic relations of acquiring or gaining material goodsrather than being viewed as a social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…New mothers are said to be ill-prepared for the transition into motherhood (Bollen, 2015;Brunton, et al, 2011;George, 2005;Smith, 1999), but that, eventually, they transform their identities to happily and readily put child-related concerns before their own (Sears & Sears, 2001). This latter idealistic scenario hides the identity crises which accompany and form part of the realities in the journey of mothering (Johnston & Swanson, 2006;Krzyżanowska, 2020;Wall, 2013). Scenarios that idealise mothering and the transition period are guided by normative ideas of what a good mother is, with no acknowledgement of how time or contexts shape new mothers' constructions of mothering in the immediate postnatal period, or how they adjust to the transition period between birth and early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…New mothers are said to be ill-prepared for the transition into motherhood (Bollen, 2015;Brunton, et al, 2011;George, 2005;Smith, 1999), but that, eventually, they transform their identities to happily and readily put child-related concerns before their own (Sears & Sears, 2001). This latter idealistic scenario hides the identity crises which accompany and form part of the realities in the journey of mothering (Johnston & Swanson, 2006;Krzyżanowska, 2020;Wall, 2013). Scenarios that idealise mothering and the transition period are guided by normative ideas of what a good mother is, with no acknowledgement of how time or contexts shape new mothers' constructions of mothering in the immediate postnatal period, or how they adjust to the transition period between birth and early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that within online spaces there is both replication of, and tension with, intensive mothering. Analysis of online representations of mothering suggests that mothers are held responsible for shaping their child(ren) (Feldman, 2021), often through consumption-focused visions of motherhood (Krzyżanowska, 2020), and that women feel a pressure to self-present online as enjoying motherhood, with well-presented children (DeGroot and Vik, 2021).…”
Section: Conceptualising Virtual Motheringmentioning
confidence: 99%
“…Over the last two decades, motherhood online has emerged as a distinct field of scholarly enquiry (Mackenzie and Zhao, 2021). Using a range of sites, apps and social media, researchers have sought to understand how motherhood is performed and represented in online spaces (Astudillo-Mendoza and Cifuentes-Zunino, 2022; Krzyżanowska, 2020; Zhao and Bouvier, 2022). Some authors have started to explore how, in the contemporary world, online activity is not something that somehow happens after the tasks of mothering, a way of representing activities that have been completed, but is actually part of doing mothering per se.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning social media influencers, a paper by Natalia Krzyżanowska explored the commodification of motherhood, and this research found that contemporary practices of commercialised self-mediation by "celebrity mothers" increasingly normalise a strongly commodified and consumption-driven vision of motherhood (Krzyżanowska, 2020). Drawing on the affordances of mediatization and self-mediation embedded on the broader neoliberal and celebrity culture mindset, the article analyses how motherhood becomes increasingly linked, in public discourses, to economic relations of acquiring or gaining material goods-rather than being viewed as a socially or individually significant process or role.…”
Section: Introductionmentioning
confidence: 99%